Communication activities of public relations and their role in building the mental image of the public in the municipalities of the governorates of Gaza - Abu draz, Ahed (Dirasat: Human and Social Sciences, 2021)
The study aims to identify the communication activities of public relations and their role in building the mental image of the public in the municipalities of the governorates of Gaza. The descriptive analytical method was adopted, and the study sample consisted of (456) publics from the municipalities of the governorates of Gaza, namely: (Gaza Municipality, Jabalia Municipality, Deir Al Balah Municipality, Khan Yunis Municipality, Rafah Municipality), and the questionnaire was used as a tool to collect data. The most important results of the study were the following: - The most communication activities used by public relations in the municipality are social media. - The Public Relations Department changes the bad impressions of the municipality and seeks to win public opinion. The study concluded with a set of recommendations, the most important of which are the following: - Introducing the municipality to the public with its departments, and the nature of the work of each department, and from the person assigned to it, to facilitate communication with them when necessary.